PERCEIVED EASE OF USE OF THE SHOPEEFOOD PLATFORM: A CASE STUDY AMONG STUDENTS OF POLITEKNIK LP3I DEPOK - Mohammad Fachri Radhian; Muhammad Rafarellian Nurjaya; Destiana Maharani (POLITEKNIK LP3I JAKARTA, 2026)
With the development of digital technology, there has been a change in student behavior in fulfilling their daily needs, particularly in ordering food through online delivery services. ShopeeFood is one of the platforms used by students. The ease of operating a platform's media is one of the factors that can influence the use of the application. This paper aims to determine the perception of ease of use of the ShopeeFood platform among students of Politeknik LP3I Depok. The research method used a qualitative approach with interview and questionnaire techniques. The informants of this study were students of Politeknik LP3I Depok from various study programs who used ShopeeFood services more than once in ordering food. Based on the research results, it shows that users rate the ShopeeFood platform as having a good level of ease of use. This ease is assessed from the process of searching for restaurants and menus, the ease of placing orders and making payments, as well as the ease of understanding the features available in the application. This research can serve as input for ShopeeFood to continue maintaining and improving the quality of ease of use of its application in order to provide a better and easier experience for users.